MOLECULAR CHARACTERS OF ENDOPHYTIC FUNGI ISOLATE FROM RUBBER LEAVES (Hevea brasiliensis) - Syamsafitri; Darma Bakti Nasution; Lisnawita; Radite Tistama (CV. Radja Publika, 2022)
Endophytic microbes can be isolated from various types of plants, one of which is from rubber leaves (Hevea brasiliensis). Rubber plants have been planted widely, which means they have the ability to adapt to environmental conditions. Apart from that, currently many rubber clones have been produced which of course harbor potential microbes in them. The potential presence of endophytic fungi can be utilized to support the growth of rubber plants. Isolation of endophytic fungi from rubber plants which have potential as biological agents for controlling diseases, one of which is leaf fall disease. The aim of this research was to determine the diversity of endophytic fungal isolates associated with rubber clone leaves using the DNA extraction method from endophytic fungi from rubber leaves. The results of PCR amplification of the genome DNA of 5 endophytic fungal isolates using primers ITS1 and ITS4 produced one DNA fragment with a size of 612 bp for Aspergillus sp. (BB1) 598 bp for Aspergillus flavus (BB2), 637 bp for Trichoderma asperelum (BB4), 610 bp for Aspergillus sp (KI1) and 621 bp for Aspergillus flavus in isolate KI3 Based on the results of BLAST analysis of the DNA fragment sequence with the fungal isolate sequence Other endophytes in the National Center for Biotechnology Information (NCBI) GeneBank show that the sequence similarity between the isolates analyzed is 99-100%.